PENEGAKAN HUKUM KEJAHATAN KORPORASI DI SEKTOR PERBANKAN - Zein, Masnur (JURNAL ILMIAH LIVING LAW, 2015)
Purpose of this research is how to tackle corporate crime in the banking company. Such identification will be investigated by the method of juridical and juridical comparative method. The results of this study indicate that the application of criminal sanctions against the perpetrators of crimes in the banking corporation is to apply criminal sanctions principal and additional penalty. Efforts are being made to combat corporate crime in the banking sector, namely the penal and non-penal efforts. Penal effort applied in the formulation and execution stages, whereas preventive measures or non-penal supervision and oversight of the efforts of the banking industry where efforts can be issued through the provisions of the decree and circulars, instructions, guidance and direction.